Wear properties of AISI 4140, steel modified with electrolytic-plasma technology - Ayday, Aysun (Materiali in tehnologije, 2013)
An electrolytic-plasma treatment (EPT) was applied to the surface of AISI 4140 steel and the wear behavior under dry sliding conditions was studied for different treatment parameters. The modified samples were characterized before and after the wear testing using metallographic, SEM-microscope and microhardness techniques. The test results indicate that the wear resistance of the AISI 4140 steel can be improved by means of electrolytic-plasma technology (EPT). The wear resistance increases with an increased modified-layer hardness due to a transformation to the martensitic structure.
Keywords: plasma; plazma; microhardness; mikrotrdota; obraba; wear